2016
DOI: 10.1088/0957-4484/27/47/475401
|View full text |Cite
|
Sign up to set email alerts
|

Control over fuel cell performance through modulation of pore accessibility: investigation and modeling of carbon nanotubes effects on oxygen reduction at N-graphene-based nanocomposite

Abstract: The lack of performance of graphene-based electrocatalysts for oxygen reduction (ORR) is a major concern for fuel cells which can be mastered using nanocomposites. This work is highlighted by the optimization of nitrogen(N)-doped graphene/carbon nanotubes (CNTs) nanocomposite's ORR performance examined by galvanostatic measurements in realistically approached glucose half-cells. Obtained results mark an essential step for the development of nanocarbon-based cathodes, as we specifically evaluate the electrode p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…277,278 The importance of pore accessibility within the surface of the catalyst was suggested by researchers using a composite of N-doped graphene and CNTs. 279 Other recent papers also report the synthesis of other metal-free catalysts for the ORR. 280−304…”
Section: Catalyst Preparation and Performancementioning
confidence: 63%
See 1 more Smart Citation
“…277,278 The importance of pore accessibility within the surface of the catalyst was suggested by researchers using a composite of N-doped graphene and CNTs. 279 Other recent papers also report the synthesis of other metal-free catalysts for the ORR. 280−304…”
Section: Catalyst Preparation and Performancementioning
confidence: 63%
“…Zheng et al used partially oxidized graphene to incorporate pyridinic N species via the substitution of O with N during NH 3 treatments and saw that pure pyridinic N species catalyzed the two-electron reduction of O 2 to H 2 O 2 . Another group investigated the influence of different N sources on the types of N species formed in the catalyst and showed that N incorporation from glycine contributed to higher catalyst activity while NH 3 treatment etched the catalyst surface, giving higher surface area and improved access of O 2 to protected active sites. , The importance of pore accessibility within the surface of the catalyst was suggested by researchers using a composite of N-doped graphene and CNTs . Other recent papers also report the synthesis of other metal-free catalysts for the ORR. …”
Section: Pyrolyzed Nonprecious Metal Catalystsmentioning
confidence: 99%